Primary antibody deficiency in adults. - Spickett, G; Misbah, SA; Chapel, H (1991)
Primary antibody deficiency is defined as a reduction or absence of one or more immunoglobulin isotypes or subclasses, when no other contributory disorder is present. Some patients may have normal serum immunoglobulin concentrations but do not respond appropriately to pathogens; such patients also have a primary antibody deficiency. There are three major forms of antibody deficiency: X-linked agammaglobulinaemia (XLA, Bruton's agammaglobulinaemia), common variable immunodeficiency (CVID), which includes IgG subclass and specific antibody deficiencies, and selective IgA deficiency.1 Other antibody deficiency syndromes are rare; in most cases clinical features, diagnosis, and treatment are similar to those of the three major deficiencies. Although all primary immunodeficiencies are rare, IgA deficiency has an estimated frequency of between 1 in 320 and 1 in 800.2 Overall, a prevalence of 11·6 per million of population is reported, of whom 6 per million have XLA, 5 per million have CVID, and the remainder have autosomal recessive antibody deficiencies.3 Swedish data suggest a higher prevalence of 20-40 per million of population.4 Most primary care physicians will never see a patient, and hospital specialists, other than immunologists, will see only 2 or 3 in a lifetime of practice. Consequences of delayed diagnosis are serious: in a study of 32 patients with primary antibody deficiency, more than two-thirds experienced diagnostic delay leading to serious morbidity.5. © 1991.